2020
DOI: 10.1037/fam0000787
|View full text |Cite
|
Sign up to set email alerts
|

Gaining a new perspective on the quality of parent–adolescent relationships from adolescent speech samples.

Abstract: Although the quality of the parent-teen relationship is key to understanding both psychopathology and well-being in adolescence, there are limited assessments of adolescents' underlying attitudes regarding their parents. This study aimed to evaluate a novel and brief method of coding adolescents' 3-min speech samples regarding their affective attitudes (e.g., thoughts and feelings) toward their parent. A community sample of 72 adolescents (M age ϭ 16 years) completed a 3-min speech sample and several questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…During 2017 and 2018, we collected three‐minute speech samples from 72 adolescents attending high schools in three Australian state, as part of a larger study on the usefulness of the Family Affective Attitude Rating Scale (FAARS), a novel method of coding affective attitudes, with adolescent populations (McKenna et al., 2020). The community sample of adolescents was asked to talk about their parent figure to explore normative adolescent experiences of adolescent–parent relationships.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During 2017 and 2018, we collected three‐minute speech samples from 72 adolescents attending high schools in three Australian state, as part of a larger study on the usefulness of the Family Affective Attitude Rating Scale (FAARS), a novel method of coding affective attitudes, with adolescent populations (McKenna et al., 2020). The community sample of adolescents was asked to talk about their parent figure to explore normative adolescent experiences of adolescent–parent relationships.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of coding systems have been adapted to quantitatively assess relationship domains, including warmth, criticism, and emotional overinvolvement, across age groups (Sher-Censor, 2015). More recently, speech samples have been used to assess the emotional climate of adolescentparent relationships (McKenna, Hassall, O'Kearney, & Pasalich, 2020;Przeworski et al, 2012;Schmidt, Tetzlaff, & Hilbert, 2015).…”
Section: Adolescent Speech Samples Regarding Their Perceptions Of Rel...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although CU traits have most often been studied in forensic or clinic‐referred samples of children and adolescents, research with community samples has indicated that these traits are often associated with similar neurocognitive characteristics regardless of whether they occur in combination with antisocial behaviour or in isolation (Viding & McCrory, 2012). In terms of language, speech analysis of adolescents' discussions with their parents in a community sample found that CU traits were positively correlated with increased negative tone and language content (McKenna et al, 2020). It has also been found that among adolescent offenders high in CU traits, higher verbal abilities predicted more violent crimes (Muñoz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%